Anti-virus effects of interferon regulatory factors (IRFs) identified in ascidian Ciona savignyi. Issue 106 (November 2020) - Zhang, Zhaoxuan; Wei, Jiankai; Ren, Ruimei; Zhang, Xiaoming
Abstract: Interferon regulatory factors (IRFs) are key transcription factors that function in the immune system via the interferon (IFN) pathway. In the current study, we identified and characterized three IRFs (CsIRFL1, CsIRFL2, and CsIRFL3) from ascidian Ciona savignyi . Phylogenetic analysis showed that CsIRFL1 was clustered with two IRFs from Ciona robusta and shrimp IRF apart from the vertebrate IRFs, whereas CsIRFL2 and CsIRFL3 were grouped with an unnamed protein from Oikopleura dioica into a sub-branch highly identifying with the vertebrate IRF4, IRF8, and IRF9. Gene expression analysis revealed that CsIRFL1 and CsIRFL2 expressed in all the examined adult tissues (stomach, intestines, eggs, hemocytes, gonad, heart, and pharynx) and predominantly in hemocytes. However, the expression of CsIRFL3 was undetectable in the tested adult tissues. Furthermore, in situ hybridization showed that CsIRFL1 and CsIRFL2 mainly expressed in immunocytes within hemolymph, including phagocytes, macrophage-like cells, morula cells, and amoebocytes, suggesting CsIRFL1 and CsIRFL2 were involved in ascidian immune responses. We then performed LPS and poly(I:C) challenge assay and found that CsIRFL1 highly expressed in the cultured hemocytes following LPS infection for 24 h. After viral analogue poly(I:C) stimulation, the expression of CsIRFL2 was dramatically upregulated from 12 to 24 h. Meanwhile, two critical components of the IFN signaling pathways, STAT and TBK1, showed the increased expression as well after poly(I:C) induction, indicating that CsIRFL2 and IFN pathways genes were activated under the infection of viral analogue. Thus, our findings suggested that CsIRFL2 was a potential transcriptional regulatory factor that participated in regulating the ascidian anti-virus immune response. Highlights: Three IRF genes (CsIRFL1, CsIRFL2, and CsIRFL3) was cloned and characterized from ascidian Ciona savignyi. CsIRFL1 and CsIRFL2 predominantly expressed in hemocytes, especially in immunocytes within hemolymph. CsIRFL1 was distributed in the cytoplasm and the nucleus of HEK293T cells; CsIRFL2 was localized in the nucleus of HEK293T cells. In cultured hemocytes, CsIRFL2 were significantly upregulated following stimulation with poly(I:C) for 24 h.